(untitled) (Research, Society and Development, 2024)
Sustainable management of water resources is essential to ensure access to quality drinking water for all populations. However, many Brazilians, especially in rural areas and isolated communities, depend on alternative water supply solutions that lack adequate assessment of water quality control. Given this scenario, this study aimed to develop and validate a Sanitary Inspection Guide for Alternative Collective Solutions (RISSAC), aiming to strengthen water quality surveillance in municipalities and contribute to the promotion of public health. Based on the analysis of existing guides and consultation with current legislation, an instrument for sanitary inspection of Alternative Collective Solutions (SACs) was developed. The first version contained 69 evaluation items and, after being subjected to a validation process by theoretical expert judges, resulted in a guide with 67 items. This second version was tested in three municipalities in Rio Grande do Sul State by practical expert judges, and employees of municipal health departments, who also validated the final version of the guide, composed of 54 items. RISSAC proved to be an adequate and objective instrument for sanitary inspections reality by municipal water surveillance agents. The results of this study highlight the importance of standardized and robust inspection instruments for water quality management and serve as a basis for the development of more effective public policies and for universal access to safe water throughout the national territory.